The rise of the randomistas: on the experimental turn in international aid - Donovan, Kevin P. (Economy and Society, 2018)
In recent years, the use of experimental methodologies has emerged as a central means of evaluating international aid interventions. Today, proponents of randomized control trials (so-called randomistas) are am ong the most influential of development experts. This paper examines t he growth of this thought collective, analysing how uncertainty has be come a central concern of development institutions. It demonstrates th at transformations within the aid industry – including the influence o f evidence-based policy, the economization of development and the retr eat from macro-planning – created the conditions of possibility for ex perimentation. Within this field, the randomistas adeptly pursued a va riety of rhetorical, affective, methodological and organizational stra tegies that emphasized the lack of credible knowledge within aid and t he ability of experiments to rectify the situation. Importantly, they have insisted on the moral worth of experimentation; indeed, the exper imental ethic has been proposed as the way to change the spirit of dev elopment. Through causal certitude, they propose to reduce human suffe ring. The rise of experimentation has not, however, eliminated accusat ions of uncertainty; rather, it has redistributed the means through wh ich knowledge about development is considered credible.
Keywords: Development; Evidence; Experimentation; aid; uncertainty